Art and science: two roads leading to the same reality (REVISTA NODO, 2011)
The article analyzes the role of art as a knowledge generator, a possibility often denied by scientists. From the point of view of semiotics and pedagogy (Schwarcz), the sociology of art (Hauser) and philosophy (Gadamer), the authors argue that art is a unique pathway to knowledge transcending the limits of science; that it is a deposit of living experiences; that it is a product of the particular historic, economic and cultural contexts; and that it currently plays a critical social role, all of which indicate how deeply it is connected to the reality giving birth to it. They also pinpoint that both art and science turn to language for their operative and communicational procedures, a strategy that is in itself a form of art composed by signs representing the absent, signs with the ability to bring the past and the future to the present. As a conclusion, the authors state that art is solidly melted into reality, which, as a totalizing phenomena linked to the social and human milieu represents society and culture in all their various manifestations.
Keywords: Sociology of art; icon; language; representation; art and science